Kinetics of Amino Acids Oxidation by Alkaline Transition Metal Complexes - M. Abdel-Halim, Hamzeh; M. Ai Lawatia, Yasmeen (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of cysteine and proline by hexacyanoferrate (III) and permanganate, respectively, has been studied in basic medium at 25ºC. The reaction rate was measured, spectrophotometrically, by following the change in the oxidizing agent concentration with time. Results showed the rate of oxidation is zero order for the alkali, first order for the oxidant, first order for substrate in the oxidation of cysteine with haxacyanoferrate (III) and an order of 0.35 for the substrate in the oxidation of proline with permanganate. The value of the rate constant for cysteine-hexacyanoferrate (III) oxidation is more than two fold of magnitude larger than that for proline-permanganate oxidation.